In Vitro Phytochemical and Inhibitory Potential Test of Bawang Hutan Bulb Extract (Eleutherine palmifolia) on Vibrio harveyi - WAODE MUNAENI; ARMAN PARIAKAN; LAODE BAYTUL ABIDIN; MUNTI YUHANA (Microbiology Indonesia, 2017)
The objectives of this study were to analyze phytochemical content of bawang hutan bulbs extract (Eleutherine palmifolia) and to test the inhibitory potential of bawang hutan bulbs extract on the growth of Vibrio harveyi bacteria at different doses. This study was conducted in March-May 2017 in Testing Laboratory of Fisheries and Marine Science Faculty of Halu Oleo University and Laboratory of Fish Health of Aquaculture Department of Fisheries and Marine Science Faculty and Laboratory of Biopharmaca of Bogor Agricultural University. Test parameter included: (1) Phytochemical test through the method of color visualization, (2) Inhibitory potential test using two methods namely agar diffusion and co-culture. Treatment of dose consisted of positive control/K+ (Chloramphenicol 30 mg/ml), negative control/K- (Sterile Aquadest) and treatment of extract included A (20 mg/ml), B (40 mg/ml), C (60 mg/ml), D (80 mg/ml). Qualitatively, result of phytochemical test showed that bawang hutan bulbs extract contained flavonoid, tannin, saponin, quinone, steroid and triterpenoid compounds. Result of inhibitory potential test indicated that treatment D obtained the highest inhibitory potential, while the minimum inhibitory potential was found in treatment A. The best co-culture test result was also found in treatment D, in which 24 hours after co-culture was performed, no V. harveyi colonies (total bacteria of 0 CFU/mL) were found. Bawang hutan bulbs extract in this study was able to inhibit the growth of V. harveyi.